DESIGNING STUDENTS WORKSHEET: A SOCIOLINGUISTICS APPROACH FOR TESTING SPEAKING AND LISTENING - Irwan Irwan (Ta'dib, 2009)
This article discusses about an approach to create a good test for speaking and listening subject.  The facts showed that many of the tests were created based on the teacher’s needs, not yet based on the goal of the test itself.  As we know, there are kinds of approach to create a good test to test language ability; speaking, reading, writing and listening.  One of them is a sociolinguistics approach.  This approach is introduced to make the students aware of the test.  To apply this approach, teacher must prepare a well-designed worksheet for the students.  The worksheet must be written completely related to the sociolinguistics approach.  In this article, the writer will explain the way of how to design a worksheet for the students especially in testing speaking and listening. Kata Kunci:  Designing, worksheet, sociolinguistics, approach, testing